2011
DOI: 10.1186/1471-2369-12-28
|View full text |Cite
|
Sign up to set email alerts
|

Defensive coping and health-related quality of life in chronic kidney disease: a cross-sectional study

Abstract: BackgroundCoping with the stresses of chronic disease is considered as a key factor in the perceived impairment of health related quality of life (HRQL). Little is known though about these associations in chronic kidney disease (CKD). The present study aimed to investigate the relationship of defensive coping and HRQL among patients in different CKD stages, after adjusting for psychological distress, sociodemographic and disease-related variables.MethodsThe sample consisted of 98 CKD patients, attending a univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 52 publications
4
27
0
5
Order By: Relevance
“…A search of the PsychInfo database using the term "rationality emotional defensiveness" showed that it appears only in 19 publications. It has demonstrated adequate internal consistency when used with other populations than breast cancer (e.g., α = .77 in a sample of university students (Ritz & Dahme, 1996) and α = .76 in chronic kidney disease (Kaltsouda et al, 2011)). …”
Section: ; Letho Et Al 2006)mentioning
confidence: 99%
“…A search of the PsychInfo database using the term "rationality emotional defensiveness" showed that it appears only in 19 publications. It has demonstrated adequate internal consistency when used with other populations than breast cancer (e.g., α = .77 in a sample of university students (Ritz & Dahme, 1996) and α = .76 in chronic kidney disease (Kaltsouda et al, 2011)). …”
Section: ; Letho Et Al 2006)mentioning
confidence: 99%
“…Based on previous studies, 2,[8][9][10]12,13,15,16,18,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] we assumed the existence of a 20% difference in the prevalence of depression between the general population and ESRD patients on HD. In order to obtain a confidence level (power) of 95% and a confidence limit of 10%, we aimed to study 246 patients (calculated using the QuesGen Systems sample size calculator).…”
Section: Sample Size Estimationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Patients suffering from chronic kidney disease have poor QOL and mental well-being, often suffering from anxiety and depression. [8][9][10] It has been reported that depression is the most common psychiatric abnormality among end-stage renal disease (ESRD) patients. [11][12][13] In terms of frequency, it is second to hypertension as a comorbid diagnosis among ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
“…SF-36 physical and Studies show that patients with chronic illnesses have lower scores for HRQOL as compared to general populations (67,(184)(185)(186). Physical HRQOL is generally more adversely affected in patients with chronic illness (184,185).…”
Section: Univariate Findingsmentioning
confidence: 99%
“…Physical HRQOL is generally more adversely affected in patients with chronic illness (184,185). In some cases such as chronic kidney disease, prolonged exposure to disease can also result in lower mental HRQOL for chronically ill patients (186).…”
Section: Univariate Findingsmentioning
confidence: 99%